Online Business Media of Ukraine: Typology and Specific Features - Nikytenko, Viktoriia (Information & Media, 2022)
This article offers a new look at the specific characteristics and key typological factors of online business media in Ukraine. Knowledge of the typological structure and features of business media segmentation can be used in marketing plans and media planning. The empirical part of the article presents a comprehensive definition of the term “business journalism” in the social communication discourse of Ukraine, as well as the typology of online business media based on selected structural and functional and type-forming factors: economic and organizational, structural and functional, professional and technological. As a result of practical analysis and theoretical thinking, the article also proposes the definition of social functions of business media, which was previously overlooked by scientists.
Keywords: online business media of Ukraine; typology; typological factors; mass communication; social communication discourse